On the Uplink Achievable Rate for Massive MIMO With 1-Bit ADC and Superimposed Pilots - M. A. Teeti; Rui Wang; Reza Abdolee (IEEE Access, 2018)
In this paper, a superimposed pilot scheme for massive multiple-input multiple-output uplink transmission with 1-bit analog-to-digital converters (ADCs) at the base station (BS) is considered. Due to the intractable complexity of obtaining true bounds on the data rate, we thus derive an approximate lower bound on the achievable data rate while assuming the BS employs the linear minimum mean square error channel estimator and maximum ratio combining receiver. The derived bound is shown to be nearly tight when the number of users is large or operating in the low signal-to-noise ratio (SNR) regime. We also obtain the closed-form expression of the optimal pilot-data power allocation maximizing the data rate. Although there is a performance gap between the quantized and unquantized (i.e., with infinite-resolution ADCs) systems, it is shown that this gap diminishes when the number of BS antennas is asymptotically large. We show that when the received pilot symbols are removed from the received signal (utilizing the estimated channel) for the data detection process, the increase in data rate is not significant when compared with the no-pilot-removal case, especially in the regimes of low SNR and a large number of users. We present some numerical results to corroborate our theoretical findings, and the insights are provided for further exploration of the quantized systems with superimposed pilots.